Instrument Development of Dynamical Modelling Skills in Computational Physics Course - Saefan, Joko; Rusilowati, Ani; Susilaningsih, Endang (Jurnal Penelitian Pembelajaran Fisika, 2024)
This research aims to develop an instrument for assessing dynamical modelling skills, especially in the Computational Physics course. The instrument was developed using a 4D model (Define, Design, Develop, Disseminate). The proposed indicators consist of basic programming capabilities, visualization tools, modeling of physical phenomena, and execution. Each indicator is reduced to more detailed statement items. There are five experts who assess the relevance of items using Likert scale format indicators. The expert validation results were analyzed using the V-Aiken equation and a score of 0.88 was obtained so that the instrument developed was said to be valid and could be used to measure dynamic modeling capabilities.